‘Buried in the Open Fields’: Early Modern Suicide and the Case of Ofelia - Janet Clare (Journal of Early Modern Studies, 2013)
Focussing on Ophelia’s suicide in Hamlet, as it is represented in the different texts of the play, this essay argues that the play mediates the diverse responses to self-murder in the early modern period. The social status of the suicide could determine the coroner’s verdict. Literary scholars have paid too little attention to the way the texts of the play are symptomatic of theological, popular and legal attitudes to early modern suicide. The culture of suicide resonates with the text in ways more complicated than some historians have assumed.